Sistem Pakar Diagnosa Hama Dan Penyakit Pada Pohon Buah Durian Menggunakan Metode Forward Chanining - Yudi Prayoga; Ahmad (CV. Multi Kreasi Media, 2024)
Durian plant is a yang plant that is much interested by durian fruit connoisseurs. Especially in the field of world trade sector. Durian fruit is also one of the country'sforeign exchange earnings. No wonder the government pays great attention to thedevelopment and quality of duran trees. However, on the other hand, theattention of durian tree farmers to their crops and the changing seasons from time to time causes durian plants to be easily exposed to disease. This certainlyhas an impact on the quality of the fruit that will be tapped and the declineof trade in Indonesia. To overcome this problem, appropriate measures are needed to control the disease of this durian tree plant, The expert system using the Forward Chaining method for diagnosing pests and diseases of durian tree plants is the best solution to recognize the symptoms of disease in rubber plants as early as possible, find out the cause of the disease and how to control it. In making this system, experts who are experts in the field of pests and diseases of durian trees are needed to obtain accurate data on disease information on durian trees. This expert system of diagnosing pests and diseases of durian trees is designed using a web-based php programming language. The design of the knowledge base in this system is dynamically created to make it easier to manage data such as adding, changing and deleting data.